RESPONSE OF WHEAT (TRITICUM AESTIVUM) TO NITROGEN AND ZINC APPLICATION - GOSWAMI, V.K (Annals of Agricultural Research, 2014)
A field experiment was conducted during winter season of 2003 on cultivar U.P. 2338 with three levels of nitrogen viz. 0, 75 and 100 kg/ha and 3 levels of zinc viz. 0, 5 and 10 kg/ha in randomized block design (RBD) with three replications.application of 100 kg N/ha and 5 kg Zn/ha to wheat variety UP 2338 results in higher yield of crop under western Uttar Pradesh conditions.